Positioning the self (nafs) in Islāmic psycho-spirituality - Rassool, G. Hussein (Journal of spirituality in mental health, 2025)
There is a significant overlap between the objectives of the Qur’ān and psychology, highlighting their interconnectedness and the importance of Islāmic psycho-spirituality. The Qur’ān provides insights into human nature, emotions, and moral frameworks which align with psychological principles. Nafs, a Qur’ānic term referring to the self, plays a vital role in Islāmic psycho-spirituality. To achieve this, Islāmic psychology emphasizes self-reflection, self-control, and self-improvement, among many other practices, similar to psychological principles. Understanding and purifying the nafs to its higher levels enables individuals to strive for moral excellence, personal growth, and a stronger connection with Allāh.